Cartographie de la susceptibilité aux glissements de terrain dans la région de Nova Friburgo (État de Rio de Janeiro, Brésil). Une étape vers l’évaluation et la gestion du risque - François Bétard; Nicolas Delbart; Clément Piel (Bulletin de l’Association de Géographes Français)
Landslides constitute a major natural hazard in Brazil, as recently shown by the disaster of January 2011 in the Rio de Janeira State that caused more than 1,500 deaths and extensive damage to the urban and rural infrastructures of the region. With the aim of improving risk management, stakeholders and policymakers must have access to landslide susceptibility maps, allowing them to identify areas of their territory where new landslides have a higher probability of being triggered in the future. This study proposes to test a method of landslide susceptibility mapping in the Nova Friburgo area - one of the most affected by the disaster of January 2011 - using an indirect approach based on a bivariate probabilistic model (weight of evidence). After a procedure of calibration/validation of the model, the results led to the completion of a final susceptibility map with five classes and also offer the opportunity to interpret the respective weight of predisposing factors used as predictive variables.